Upper ocean hydrology of the Northern Humboldt Current System at seasonal, interannual and interdecadal scales. (July 2018) - Grados, Carmen; Chaigneau, Alexis; Echevin, Vincent; Dominguez, Noel
Highlights: A seasonal climatology of the NHCS was constructed gathering 50-year of in situ hydrological measurements. Alongshore and cross-shore thermohaline properties and geostrophic circulation show strong variability at a seasonal scale. Abrupt changes in T/S fields are found in the water column during El Nino and La Nina periods. Decadal variability also impacts the Peru upwelling system. Abstract: Since the 1960s, the Instituto del Mar del Perú (IMARPE) collected tens of thousands of in-situ temperature and salinity profiles in the Northern Humboldt Current System (NHCS). In this study, we blend this unique database with the historical in-situ profiles available from the World Ocean Database for the period 1960–2014 and apply a four-dimensional interpolation scheme to construct a seasonal climatology of temperature and salinity of the NHCS. The resulting interpolated temperature and salinity fields are gridded at a high spatial resolution (0.1° × 0.1° in latitude/longitude) between the surface and 1000 m depth, providing a detailed view of the hydrology and geostrophic circulation of this region. In particular, the mean distribution and characteristics of the main water-masses in the upper ocean of the NHCS are described, as well as their seasonal variations between austral summer and winter. The coastal upwelling region is well documented due to the increased data density along 3 highlighted cross-shore vertical sections off Paita (∼5°S), Chimbote (∼9°S) and San Juan (∼16.5°S). The large and long-term database also allowed us, through a composite analysis, to investigate the impact of the eastern Pacific El Niño and La Niña events on the NHCS hydrology. On average, during these periods, large temperature (±3–4 °C) and salinity (±0.1–0.2) anomalies are observed, impacting the water column of the coastal ocean off Peru down to 100–200 m depth. At 100 km from the coast, these anomalies are associated with a maximum deepening (shoaling, respectively) of the thermocline of 60 m (25 m) during composite El Niño (La Niña) events. At interdecadal scale, a similar approach reveals sea-surface temperature variations of ±0.5°C, associated with a deepening (shoaling) of the thermocline of 5–10 m during warm (cold) periods.